Kinetics and Mechanistic Studies of Oxidation of V(IV) by ICl and IBr in Aqueous Acetic Acid and Perchloric Acid Medium - Radhakrishna Murti, P.S.; S. Triphathy, Kiran; Ahmed, Ejaz (Asian Journal of Chemistry, 2010)
A kinetic study on the oxidation of V(IV) by iodine monochloride (ICI) and iodine monobromide (IBr) in aqueous acetic acid and perchloric acid media has been carried out. In both the systems studied the order with respect to oxidant is unity. In case of lCI the dependence on [substrate] is fractional whereas in [IBr] it is unity. The order with respect to [H+] in ICI and IBr reactions is inverse fractional. The rate of reaction remains invariant to the change in composition of a complex between the hydrolysed species of V(IV) and the effective species of the oxidant in a reversible equilibrium.